2008
DOI: 10.1016/j.ijpharm.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid vector including polyethylenimine and cationic lipid, DOTMA, for gene delivery

Abstract: We developed polyethylenimine (PEI) After intravenous injection of the lipopolyplexes into mice, high gene expression in the liver, spleen, and lung was observed with lipopolyplex 2P-2D, lipopolyplex 2P-4D, and polyplex 8P. In particular, lipopolyplex 2P-4D showed the highest gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…This indicates that the success of lipopolyplexes relies on a loosely condensed polyplex core modified by a moderate amount of lipid. Interestingly, earlier studies have also reported that the highest enhancement of transfection by PEI and DOTAP-Chol or DOTMA was achieved at relatively low PEI/DNA ratios of 4.5 23 and 2, 21 respectively, although the reason for this was unclear. It is possible that the relaxed polyplex core benefited transfection by achieving a balance between DNA protection and subsequent DNA liberation for gene expression.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This indicates that the success of lipopolyplexes relies on a loosely condensed polyplex core modified by a moderate amount of lipid. Interestingly, earlier studies have also reported that the highest enhancement of transfection by PEI and DOTAP-Chol or DOTMA was achieved at relatively low PEI/DNA ratios of 4.5 23 and 2, 21 respectively, although the reason for this was unclear. It is possible that the relaxed polyplex core benefited transfection by achieving a balance between DNA protection and subsequent DNA liberation for gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that cationic lipids formed an outer coat around the preformed polyplexes, in agreement with the "core-shell" structure of lipopolyplexes proposed by earlier studies. 21,22 Nevertheless, it should be noted that the surface charge of lipopolyplexes also increased with increasing PEI/ DNA ratio. Thus, it is possible that the polyplex core was not entirely wrapped by the lipids, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by electron microscopy have been suggested that lipopolyplexes prepared by this method have viruslike structure. In this structure, the central core consists of polycation-DNA and lipid bilayers make its shell and also particle's surface properties to be determined by liposome [10,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Covalent and non-covalent modifications of liposomes have been evaluated in several studies for improved DNA and siRNA delivery [7][8][9][10][11][12][13][14][15]. It has been reported that a combination of low molecular (700 and 2000 Da) and high molecular weight (22 and 25 KDa) PEIs resulted in an improvement of transfection efficiency in vitro [7,11].…”
Section: Introductionmentioning
confidence: 99%